Cone-beam computed tomography study of prevalence and location of MB2 canal in the mesiobuccal root of the maxillary second molar - Betancourt, Pablo (Int J Clin Exp Med, 2015)
The maxillary second molar (2 MM) has the most complex root canal system, and a high percentage of treatment failures is due to the impossibility of locating, instrumenting and obturating the second mesiobuccal canal (MB2). The aim of this study was to describe in vivo the prevalence and location of the MB2 canal in the mesiobuccal root of the permanent maxillary second molar through CBCT image analysis. Two hundred twenty five CBCT images of 2 MM were studied. In the presence of the MB2 canal, the floor of the coronal cavity was located and advanced every 1 mm apically to standardize observation. The geometric location in relation to the primary mesiobuccal (MB1) and palatal (P) canals was done by locating the central points of the canal and projecting a line between them, together with a perpendicular line between MB1-P (point T). The data were analyzed using descriptive statistics, with a value of P < 0.05 being statistically significant. The MB2 canal was identified in 48% of the cases. It was located 2.2 ± 0.54 mm palatally and 0.98 ± 0.35 mesially to the MB1 canal. The average age of the subjects where it was found was 26.36 ± 10.85 years. Its location was more frequent in men (63%), and no differences were observed in its appearance in the hemi-arch. It is necessary to know the high probability of finding the MB2 canal in the maxillary second molar, and the CBCT is a good diagnostic tool for its detection and exploration.